Oil Well Fordacos – Nigeria - Adiko, Serge-B.; A. Kemalov, Ruslan. (International Journal of Engineering and Technology, 2018)
In this article we will touch upon one of the most important oil region in Africa, the Niger Delta, it is located in southern Nigeria, with an area of about 292,407.m2 Niger Delta knows how geological feature, offer huge reserves of hydrocarbons. The stratigraphic sequence of the Niger Delta consists of three broad lithostratigraphically. Units and its geochemical analyses of rocks have shown that clays from the lower coastal plain, marine Delta sediments (prodelta) and completely marine areas can be enriched with both terrestrial plant material and non-structural organic matter. That is an indicator of wealth.Forcados (forcados) in the Niger Delta province and follow plays a crucial role in the Nigerian economy and the world oil exchange. Forkados field, its physical and geographical location, Characteristics, molar and mass content of oil composition